Evaluation of urinary N-acetyl-beta-D-glucosaminidase as a marker of early renal damage in patients with type 2 diabetes mellitus - Bouvet, Beatriz Reina (2014)
Fil: Fil: Bouvet, Beatriz Reina. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Departamento de Bioquímica Clínica; Argentina.